MSME Work Ethic in West Java in Dealing the Challenge of ASEAN Economic Community (MEA) - Harding, Diana; Limakrisna, Nandan; Lestari Kadiyono, Anissa; Gunawan, Gianti (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study is to know how the work ethic and its dimensions on the MSMEs in West Java can support the efforts to face MEA and what factors can contribute the work ethic of MSMEs in West Java to face MEA. The research method used is quantitative method, with cross sectional design approach in labor force in West Java (age range 15-64 years) especially perpetrators of MSME of shoe centers in Bandung city. The instrument used in this study is work ethic from Miller’s theory (2002). Consists of seven dimensions; Self reliance, morality / ethics, leisure, hard work, centrality of work, wasted time, and delay of gratification. This instrument consists of 24 items. The score of reliability is 0.860 and categorize to quite high reliability. Category of work ethic devided into 4 category; high, quite higy, quite low, and low/ Sample size of this study is 102 respondents from 14 shoe centers in Bandung city, consisting of owner, employees, and craftmen. The results of this research indicate that, the perpetrators of MSME have a work ethic with high category as much as 43 (42%) respondents with details of 7 people owner, 30 employees and 6 craftsmen. The perpetrators of MSME are dominated by quite high category as many as 59 respondents (58%) with 7 persons, 38 employees and 6 craftsmen. The majority of respondents are in the high category on the dimensions of morality / ethics, hard work, and wasted time. Meanwhile, for other dimensions, the majority are in quite high category, are self-reliance, leisure, centrality of work, and delay of gratification. In addition, there is also a different test of demographic data to see the relationship between demography and work ethic. Demographic data obtained, internal factors that affect the work ethic is the age and the length of work.